2013
DOI: 10.1021/ja4083599
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Carbon Disulfide Production via Charge Transfer Quenching of Quantum Dots

Abstract: Carbon disulfide, a potentially therapeutic small molecule, is generated via oxidative cleavage of 1,1-dithiooxalate (DTO) photosensitized by CdSe quantum dots (QDs). Irradiation of DTO−QD conjugates leads to λ irr independent photooxidation with a quantum yield of ∼4% in aerated pH 9 buffer solution that drops sharply in deaerated solution. Excess DTO is similarly decomposed, indicating labile exchange at the QD surfaces and a photocatalytic cycle. Analogous photoreaction occurs with the O-tert-butyl ester t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…In this context, we describe the kinetics of CS 2 dissociation from several prepared TTC – salts in aqueous solution. The latter studies complement earlier investigations of CS 2 generation by photosensitized oxidation of 1,1-dithiooxalate 7 and by the thermal decay of dithiocarbamate anions. 8 The CS 2 release rates from the latter precursors vary considerably, thereby providing a wide range of activities for physiological experiments.…”
Section: Introductionsupporting
confidence: 82%
“…In this context, we describe the kinetics of CS 2 dissociation from several prepared TTC – salts in aqueous solution. The latter studies complement earlier investigations of CS 2 generation by photosensitized oxidation of 1,1-dithiooxalate 7 and by the thermal decay of dithiocarbamate anions. 8 The CS 2 release rates from the latter precursors vary considerably, thereby providing a wide range of activities for physiological experiments.…”
Section: Introductionsupporting
confidence: 82%
“…This procedure was similar to that described by Schwack and Nyanzi 52 and to that used to detect CS 2 released by the photolysis of CdSe quantum dots surface decorated with 1,1-dithiooxalate. 25 In the present case, the CS 2 was detected by determining absorption spectral changes upon reaction with alkaline ethanol to form sodium ethylxanthate ( λ max 303 nm, ε = 1.74 × 10 4 M –1 cm –1 ). 53 The DTC substrates were allowed to degrade completely (as monitored from their characteristic absorption spectra), then flowing medical grade air was used to transfer the volatile CS 2 from the substrate solution via PEEK or Teflon tubing to a stirred cuvette containing 3.0 mL of ∼10 mM NaOH in 190 proof ethanol.…”
Section: Methodsmentioning
confidence: 92%
“…Advances in understanding the biological signalling and therapeutic roles of the known SMBs have depended in part upon the accessibility of molecular species that provide controlled release under physiological conditions. 19 24 In complement to earlier studies of CS 2 release by photosensitized decomposition of 1,1-dithiooxalate, 25 the present study is an investigation of thermally activated CS 2 donors with the goal of providing a toolbox of compounds with well-defined release rates that can be used to evaluate potential signalling and/or therapeutic properties of CS 2 . In this context, we note the recent reports by Powell et al 26 and by Steiger et al 27 29 of donors for carbonyl sulfide (OCS), which serves as a precursor for the release of H 2 S, a known SMB in human physiology.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Most recently, Ford and co-workers found that 1,1-dithiooxalate bound to the surfaces of CdSe QDs can be converted into carbon disulfide under aerobic conditions through oxidative cleavage. [6] Herein, we report that visible-light irradiation of CdSe QDs leads to virtually quantitative coupling of a variety of thiols to give disulfides and molecular hydrogen without the need for sacrificial reagents or external oxidants and with relatively high turnover numbers (TONs). The mechanistic insights presented offer a blueprint for how these QDs may be used in other applications.Coupling reactions are useful in the synthesis of new molecules, as well as for various medical, biological, materials, and nanotechnological applications.…”
mentioning
confidence: 99%